2021
DOI: 10.1002/lno.11919
|View full text |Cite
|
Sign up to set email alerts
|

Supply‐controlled calcium carbonate dissolution decouples the seasonal dissolved oxygen andpHminima in Chesapeake Bay

Abstract: Acidification can present a stress on organisms and habitats in estuaries in addition to hypoxia. Although oxygen and pH decreases are generally coupled due to aerobic respiration, pH dynamics may be more complex given the multiple modes of buffering in the carbonate system. We studied the seasonal cycle of dissolved oxygen (DO), pH, dissolved inorganic carbon, total alkalinity, and calcium ion (Ca 2+ ) along the main channel of Chesapeake Bay from May to October in 2016. Contrary to the expected co-occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…It has to be mentioned that the empirically modeled TA we used in this analysis was relatively conservative to salinity, but recent observational studies have shown non-conservative behavior of TA associated with processes beyond aerobic respiration. 26,30 We used limited 1 year observed, non-conservative TA in the box model and found ∼15% higher rates of P DIC,non-aerobic , suggesting that our approach may be biased. Future work with a new set of TA observations could help constrain this source of uncertainty.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has to be mentioned that the empirically modeled TA we used in this analysis was relatively conservative to salinity, but recent observational studies have shown non-conservative behavior of TA associated with processes beyond aerobic respiration. 26,30 We used limited 1 year observed, non-conservative TA in the box model and found ∼15% higher rates of P DIC,non-aerobic , suggesting that our approach may be biased. Future work with a new set of TA observations could help constrain this source of uncertainty.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The decoupling of eutrophication-induced deoxygenation and acidification in late summer in Chesapeake Bay is consistent with recent hypotheses. 30 A possible mechanism is that nutrient inputs stimulate the generation and transport of CaCO 3 that later supports carbonate dissolution and alkalinity generation in hypoxic bottom waters. Recent reports have suggested that CaCO 3 dissolution is a dominant contributor of alkalinity in Chesapeake Bay in late summer, which can elevate pH, 30 but there is no evidence that this dissolution occurs at higher rates in years of elevated nutrient loading.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The counterbalance between OA and river basification [161] results in the most variability in the pH and carbonate chemistry in the autotrophic midbay [162], with strong pH fluctuations driven by phytoplankton photosynthesis. Additionally, seasonally, calcium carbonate dissolution is an important buffering mechanism for bottom water pH changes in late summer in the midbay, leading to higher pH values in August than in June despite persistent hypoxic conditions during the summer [146,163,164]. Wind-driven lateral upwelling can advect deep water with low pH onto shallow shoals and reduce the aragonite saturation state, potentially exposing a large fraction of oyster beds in the main stem of the bay to undersaturated carbonate mineral conditions during wind events [165,166].…”
Section: 3mentioning
confidence: 99%
“…Due to the counter-balance between OA and river alkalinization (Shen et al, 2020), pH in the autotrophic mid-bay has shown no significant long term trends but displays strong short-term fluctuations likely associated with phytoplankton photosynthesis. Also, seasonally, calcium carbonate dissolution is an important buffering mechanism for pH changes in late summer in the mid-bay, leading to higher pH values in August than in June, despite persistent hypoxic conditions during the summer (Su et al, 2020;Su et al, 2021). How these long term pH trends and seasonal variations affect seasonal development of HABs and how the increasing atmospheric pCO 2 in a warming climate influence HABs are largely unknown but are of critical importance for managing coastal resources.…”
Section: Introductionmentioning
confidence: 99%